2015
DOI: 10.1039/c5ra13157j
|View full text |Cite
|
Sign up to set email alerts
|

Plant-mediated synthesis of Au–Pd alloy nanoparticles supported on MnO2nanostructures and their application toward oxidation of 5-(hydroxymethyl)furfural

Abstract: The bio-reduction of Au(iii) and Pd(ii) was first applied to the loading process. Au–Pd/MnO2was first applied in oxidation of HMF. The effects of Au–Pd molar ratio and the support morphology on the catalysis were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Bimetallic catalysts of Au have also been efficiently explored for the oxidative upgradations of furans . Pasini et al.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
See 1 more Smart Citation
“…Bimetallic catalysts of Au have also been efficiently explored for the oxidative upgradations of furans . Pasini et al.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…In the same direction, studies showed that Pt catalysts supported on activated carbon functionalized with oxygen containing functional groups such as carboxyl group also displayed higher activity towards the oxidation of HMF to FDCA . Similarly, bimetallic Au‐Pd nanoparticles supported on MnO 2 (Au‐Pd/MnO 2 ) exhibited higher catalytic activity towards the selective oxidation of HMF to DFF as compare to the monometallic catalyst and achieved upto 98 % selectivity at 90 °C under O 2 atmosphere in 6 h …”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…Au‐nanoparticles‐based catalysts have been widely used in oxidation reactions because of their high affinity towards oxygen . Therefore, several groups have explored monometallic Au and bimetallic Au–Cu and Au–Pd catalysts for the selective oxidation of 5‐HMF to FDCA . As the Au catalysts showed some deactivation in the presence of carboxylate products, most of these reactions were performed under the high pressure (20 bar) of O 2 gas and in several cases with strong base, NaOH, to achieve high selectivity to FDCA .…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] Therefore, several groups have explored monometallic Au and bimetallic Au-Cu and Au-Pd catalysts for the selectiveo xidation of 5-HMF to FDCA. [40][41][42][43][44][45][46][47] As the Au catalysts showeds omed eactivation in the presenceo fc arboxylate products,m ost of these reactions were performed under the high pressure (20 bar) of O 2 gas and in several cases with strongb ase, NaOH, to achieve high selectivity to FDCA. [39][40][41][42][43][44][45][46][47] Other than Au catalysts, Pt-, Ru-and Pd-based catalysts were Bimetallic Ni 1Àx Pd x (0.10 x 0.75) alloy nanoparticle catalysts were synthesised and successfully employed for the catalytic aerial oxidationo fb iomass-derived furans, such as 2-furfuraldehyde (furfural), 2-furfuryla lcohol (furfuryla lcohol), 5-hydroxymethyl-2-furfural (5-HMF), 5-methyl-2-furfural (MF) and 5methyl-2-furfuryl alcohol (MFA), to selectively afford the corresponding furan carboxylic acids (2-furoic acid, furan-2,5-dicarboxylic acid (FDCA)a nd 5-methyl-2-furoic acid (MFCA)) in water at 80 8C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation